Is time-restricted eating a healthy choice to lose weight? Investigating by qualitative analysis of Instagram posts and systematic reviews with meta-analysis - Qinghao Guan; Weishan Mai; Ziyi Qiu; Yifan Zuo (Digital Health)
Background Time-restricted eating (TRE) has garnered widespread attention as a promising strategy for weight management and metabolic health improvement. Objective This study employs a mixed-methods approach to investigate the portrayal and effectiveness of TRE, bridging social media narratives and scientific evidence. Methods The first study analyzed Instagram posts qualitatively to identify prevalent TRE methods and motivations, while the second study conducted a meta-analysis of 14 randomized controlled trials (RCTs) to evaluate TRE's efficacy in weight management. Results Social media analysis revealed that the keto and 16:8 TRE method dominate online discussions, with fat loss and general health as primary motivators. High-frequency accounts shape public perception through grassroots narratives and consistent engagement. The meta-analysis found the 16:8 method to be significantly effective, particularly for individuals aged 40–50 and during short-term interventions (≤8 weeks). However, challenges such as reduced adherence in older adults, lower effectiveness in longer interventions, and inconsistent results from non-16:8 methods highlight the need for tailored strategies. Conclusion This study provides a comprehensive understanding of TRE, bridging social media narratives and scientific evidence. It identifies the mechanisms and contexts where the 16:8 TRE method is most effective and offers practical insights for individuals and professionals seeking evidence-based dietary strategies.